2017
DOI: 10.1310/hpj5204-308
|View full text |Cite
|
Sign up to set email alerts
|

A Just Culture Approach to Managing Medication Errors

Abstract: Medication errors continue to be a concern of health care providers and the public, in particular how to prevent harm from medication mistakes. Many health care workers are afraid to report errors for fear of retribution including the loss of professional licensure and even imprisonment. Most health care workers are silent, instead of admitting their mistake and discussing it openly with peers. This can result in further patient harm if the system causing the mistake is not identified and fixed; thus self-deni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…They also prove that the psychological barrier that accompanies reporting, often perceived as whistblowing, was dealt fairly well. It should be added that the trust and the possibility of reporting adverse events and mistakes freely are the basic pillars of just culture (Force et al, 2006;Rogers et al, 2017). As a result of research carried out by Paradiso and Swenney (2017) it was confirmed strong positive correlation between trust and "just culture" alignment.…”
Section: Research Results and Discussionmentioning
confidence: 93%
“…They also prove that the psychological barrier that accompanies reporting, often perceived as whistblowing, was dealt fairly well. It should be added that the trust and the possibility of reporting adverse events and mistakes freely are the basic pillars of just culture (Force et al, 2006;Rogers et al, 2017). As a result of research carried out by Paradiso and Swenney (2017) it was confirmed strong positive correlation between trust and "just culture" alignment.…”
Section: Research Results and Discussionmentioning
confidence: 93%
“…A concept called just culture , introduced by Marx (2001) was one reaction to increasing medical error trends; just culture promotes open communication and transparency focused on a purpose. A just culture uses justice to balance punishment and guiltlessness to engender a climate of open communication and impartiality (Rogers et al , 2017). Just culture is an objective of authentic leadership.…”
Section: Theme: Leadership Approachesmentioning
confidence: 99%
“…Although a nonpunitive approach is appropriate for most errors, individuals are accountable if they deliberately or repeatedly compromise patient safety. 26…”
Section: Promoting Safety Culturementioning
confidence: 99%